2022
DOI: 10.48550/arxiv.2201.12552
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relativistic description of dense matter equation of state and compatibility with neutron star observables: a Bayesian approach

Tuhin Malik,
Márcio Ferreira,
B. K. Agrawal
et al.

Abstract: The general behavior of the nuclear equation of state (EOS), relevant for the description of neutron stars (NS), is studied within a Bayesian approach applied to a set of models based on a density dependent relativistic mean field description of nuclear matter. The EOS is subjected to a minimal number of constraints based on nuclear saturation properties and the low density pure neutron matter EOS obtained from a precise next-to-next-to-next-to-leading order (N 3 LO) calculation in chiral effective field theor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…The objective of the present study is to confront the phenomenological hyperonic interaction to the recently observed neutron star properties (like mass M , radius R and tidal deformability Λ), and perform Bayesian inference for the hyperon-meson coupling constants from the robust LIGO/Virgo tidal measurement of the GW170817 binary neutron star merger (Abbott et al 2017) 1 as well as two NICER mass-radius measurements of pulsars [PSR J0030+0451 (Riley et al 2019;Miller et al 2019) and PSR J0740+6620 (Riley et al 2021;Miller et al 2021)]. Previously, such kind of Bayesian analysis on nuclear matter parameters has been performed in, e.g., Traversi & Char (2020); Imam et al (2022); Malik et al (2022), we here focus on the hypernuclear matter based on a set of six generally-used relativistic mean-field (RMF) Lagrangians. We consider two different classes of the RMF models, one with constant couplings and nonlinear meson terms in the Lagrangian [NL3ωρ (Horowitz & Piekarewicz 2001), PK1 (Long et al 2004)] and a second one without these terms but introducing density-dependent coupling strengths [DD-LZ1 (Wei et al 2020), DD-ME2 (Lalazissis et al 2005), DD2 (Typel et al 2010), PKDD (Long et al 2004)], which all treat effectively the in-medium properties of baryon-baryon interaction.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of the present study is to confront the phenomenological hyperonic interaction to the recently observed neutron star properties (like mass M , radius R and tidal deformability Λ), and perform Bayesian inference for the hyperon-meson coupling constants from the robust LIGO/Virgo tidal measurement of the GW170817 binary neutron star merger (Abbott et al 2017) 1 as well as two NICER mass-radius measurements of pulsars [PSR J0030+0451 (Riley et al 2019;Miller et al 2019) and PSR J0740+6620 (Riley et al 2021;Miller et al 2021)]. Previously, such kind of Bayesian analysis on nuclear matter parameters has been performed in, e.g., Traversi & Char (2020); Imam et al (2022); Malik et al (2022), we here focus on the hypernuclear matter based on a set of six generally-used relativistic mean-field (RMF) Lagrangians. We consider two different classes of the RMF models, one with constant couplings and nonlinear meson terms in the Lagrangian [NL3ωρ (Horowitz & Piekarewicz 2001), PK1 (Long et al 2004)] and a second one without these terms but introducing density-dependent coupling strengths [DD-LZ1 (Wei et al 2020), DD-ME2 (Lalazissis et al 2005), DD2 (Typel et al 2010), PKDD (Long et al 2004)], which all treat effectively the in-medium properties of baryon-baryon interaction.…”
Section: Introductionmentioning
confidence: 99%
“…6, we plot the density dependence of symmetry energy curvature parameter K sym against baryon number density for all of our different models corresponding to different symmetry energy(J 1 ). We also compare the range of K sym at saturation density K sym,0 ∈ [−177, 71] MeV obtained from RMF within the Bayesian Inference approach with the minimal constraint imposed [26,74]. All of our models show good agreement with the value at saturation density except the model with J 1 = 25.2 MeV.…”
Section: Resultsmentioning
confidence: 81%
“…Based on the current knowledge of nuclear masses and giant dipole polarizability, the symmetry energy has been constrained J 0 32.25 ± 2.5 MeV [16][17][18][19] and it's slope parameter L 0 58.9 ± 16 MeV [4,[20][21][22][23][24] at nuclear saturation density. However, there are very few known theoretical constraints on K sym,0 and constraints on Q sym,0 [24][25][26] and therefore, one of our objectives here is to analyze their interdependence with a model based on microphysics. Numerous relativistic mean-field models (RMF) [27][28][29][30][31] are known to have been successfully applied theoretically to extract finite nuclear properties across the periodic table as well as in applications of nuclear matter.…”
Section: Introductionmentioning
confidence: 99%
“…The secondary of GW190814 might be either a BH or a NS. The non-detection of any electromagnetic counterparts [475][476][477][478][479][480][481][482][483][484][485], the fact that there were neither clear signatures of tides or spin-induced quadrupole effects in the waveform [486,487], and the uncertainties on both the theoretical estimates of the maximum NS mass and the NS equation of state [488][489][490][491], prevent us to determine the nature of the compact object. Post-merger electromagnetic studies suggest that the merger product of GW170817 likely collapsed into a (highly-spinning) BH with a mass comparable to GW190814's secondary (∼2.6 M ) [492].…”
Section: Gw190814mentioning
confidence: 99%